Indoor air quality in elementary schools of Lisbon in spring - Pegas, P. N. (2019)
Analysis of indoor air quality (IAQ) in schools usually reveals higher levels of pollutants than in outdoor environments. The aims of this study are to measure indoor and outdoor concentrations of NO2, speciated volatile organic compounds (VOCs) and carbonyls at 14 elementary schools in Lisbon, Portugal. The investigation was carried out in May–June 2009. Three of the schools were selected to also measure comfort parameters, such as temperature and relative humidity, carbon dioxide (CO2), carbon monoxide (CO), total VOCs, and bacterial and fungal colony-forming units per cubic metre. Indoor concentrations of CO2 in the three main schools indicated inadequate classroom air exchange rates. The indoor/ outdoor (I/O) NO2 ratio ranged between 0.36 and 0.95. Atthethreemainschools,thetotalbacterialandfungal colony-forming units (CFU) in both indoor and outdoor air were above the advised maximum value of 500 CFU/m3 deﬁned by Portuguese legislation. The aromatic compounds benzene, toluene, ethylbenzene andxylenes,followedbyethers,alcoholsandterpenes, were usually the most abundant classes of VOCs. In general, the indoor total VOC concentrations were markedly higher than those observed outdoors. At all locations, indoor aldehyde levels were higher than those observed outdoors, particularly for formaldehyde. The inadequate ventilation observed likely favours accumulation of pollutants with additional indoor sources.